2022
DOI: 10.3390/en15144954
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Natural Fermented Foods as a Source for New Efficient Thermotolerant Yeasts for the Production of Second-Generation Bioethanol

Abstract: Considering the cost-effectiveness of bioethanol production at high temperatures, there is an enduring need to find new thermotolerant ethanologenic yeasts. In this study, a total of eighteen thermotolerant yeasts were isolated from various natural fermented products in Morocco. Ethanol production using 50 g/L glucose or 50 g/L xylose as the sole carbon source revealed potential yeasts with high productivities and volumetric ethanol productivities at high temperatures. Based on molecular identification, the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…Morphologically distinct isolates from a given fermented beverage were considered different yeast species and/or strains and were designated differently (data not shown). This is in agreement with several reports that states traditional fermented beverages are an important niche for yeasts in general and ethanol producing yeasts in particular [ 47 , 68 , 69 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Morphologically distinct isolates from a given fermented beverage were considered different yeast species and/or strains and were designated differently (data not shown). This is in agreement with several reports that states traditional fermented beverages are an important niche for yeasts in general and ethanol producing yeasts in particular [ 47 , 68 , 69 ].…”
Section: Resultssupporting
confidence: 93%
“…However, none of them ferment and assimilate arabinose, mannitol, lactose, xylose and starch ( Sd Table 5 and 6 ) . This is in line with the reports of [ 41 , 42 , 47 ], investigated that most yeast isolates ferment and assimilate glucose, sucrose, maltose, fructose and galactose. In addition, [89] investigated that among 90 Saccharomyces species tested, the majority of strains showed a very poor metabolic index for arabinose and xylose.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The focus of our investigation was on identifying thermotolerant yeasts from various samples across different regions, crucial for their potential in industrial applications. Notably, yeasts capable of thriving at 40 • C were considered thermotolerant in our study [40]. To situate our findings, several studies have identified the significance of natural fermented foods, soil and plants as promising sources for isolating thermotolerant yeasts.…”
Section: Isolation Of Thermotolerant Yeastssupporting
confidence: 56%